ATM Kinase-Dependent Regulation of Autophagy: A Key Player in Senescence? - Stagni, Venturina; Ferri, Alessandra; Cirotti, Claudia; Barilà, Daniela (Frontiers in Cell and Developmental Biology, 2021)
Increasing evidence suggests a strong interplay between autophagy and genomic stability. Recently, several papers have demonstrated a molecular connection between the DNA Damage Response (DDR) and autophagy and have explored how this link influences cell fate and the choice between apoptosis and senescence in response to different stimuli. The aberrant deregulation of this interplay is linked to the development of pathologies, including cancer and neurodegeneration. Ataxia-telangiectasia mutated kinase (ATM) is the product of a gene that is lost in Ataxia-Telangiectasia (A-T), a rare genetic disorder characterized by ataxia and cerebellar neurodegeneration, defects in the immune response, higher incidence of lymphoma development, and premature aging. Importantly, ATM kinase plays a central role in the DDR, and it can finely tune the balance between senescence and apoptosis: activated ATM promotes autophagy and in particular sustains the lysosomal-mitochondrial axis, which in turn promotes senescence and inhibits apoptosis. Therefore, ATM is the key factor that enables cells to escape apoptosis by entering senescence through modulation of autophagy. Importantly, unlike apoptotic cells, senescent cells are viable and have the ability to secrete proinflammatory and mitogenic factors, thus influencing the cellular environment. In this review we aim to summarize recent advances in the understanding of molecular mechanisms linking DDR and autophagy to senescence, pointing out the role of ATM kinase in these cellular responses. The significance of this regulation in the pathogenesis of Ataxia-Telangiectasia will be discussed.